Research on the Mechanical Performance and Force Transmission Mechanism of the Hybrid Tower Joint Section in Cable-stayed Bridges Under Eccentric Loading - SUN Ying; ZHENG Jialong; ZHUO Weidong; LIN Daojin; SU Shaoling (工程科学与技术)
This study considers the joint segment of the hybrid tower of Qiyun Bridge in Fu'an City as the research object to explore the mechanical characteristics of the hybrid tower joint segment of a cable-stayed bridge under eccentric load. It clarifies the mechanical performance and force transmission mechanism of the joint segment under eccentric load and the reasonable range of parameters affecting the force transmission efficiency using test and numerical analysis. The results indicated that the high safety coefficient, reliable working performance, and low stress level are the main characteristics of the bearing capacity of the hybrid tower joint segment with the rear bearing plate. The stress performance of the joint segment under the action of vertical eccentric load conforms to the force characteristics of eccentric compression components, and the strain is symmetrically distributed in the section. The bearing plate and the shear connector play a vital role in the load transfer, as demonstrated by the strain change of the steel plate (shell) near the bearing plate, and the shear force borne by the shear key near the bearing plate is greater than that of the stud shear key. In addition, the vertical load is effectively transmitted in the joint segment. The transfer efficiency of the load in the joint segment is greatly affected by the thickness of the bearing plate and the shear stiffness of the shear connector. The transfer efficiency increases initially and then tends to stabilize with the increase in the thickness of the bearing plate or the shear stiffness of the shear connector. When the shear key stiffness increases to more than 10 times the original design shear stiffness or the thickness of the bearing plate exceeds 16 mm, the load transfer efficiency remains basically unchanged. In addition, there is an apparent transmission length within the joint segment, which is about 3 m. Beyond this length, the bearing ratio of the steel shell and the filled concrete is basically close to the section stiffness ratioof the joint segment. The steel shell and the concrete, respectively, bear about 50% of the vertical load after the force transfer. The research results provide guidance and reference for the design of similar projects.